Analisis Pengaruh Implementasi Network Centric Warfare (NWC) Terhadap Interoperabilitas Operasi Keamanan Laut di Koarmada II - Habiby Achmad; Hendrik Kurniawan; Bagus Jatmiko (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The transformation of modern defense strategy has shifted from platform-centric to network-centric approaches, as reflected in the concept of Network Centric Warfare (NCW). This study aims to analyze the influence of NCW implementation on interoperability in maritime security operations within the Indonesian Navy’s Second Fleet Command (Koarmada II). A quantitative approach was used through a survey of 60 Indonesian Navy personnel directly involved in maritime security operations. Data were analyzed using descriptive statistics, Pearson correlation, and simple linear regression. The results show that both NCW implementation and interoperability levels in Koarmada II are categorized as high. The correlation test indicates a strong and significant relationship between NCW implementation and interoperability (r = 0.721; p < 0.01). Regression analysis reveals that NCW accounts for 46.8% of the variation in interoperability. These findings confirm that NCW plays a strategic role in enhancing the effectiveness of inter-unit cooperation in maritime operations. The study concludes that the success of interoperability is not only determined by networked technology but also by personnel readiness, procedural integration, and joint training practices that support the networked maritime defense concept.